Status of the Galena Mountain caribou herd - Robinson, Scott R. (Rangifer, 1991)
A resident herd of caribou (Rangifer tarandus granti) inhabits the Koyukuk River valley and Kokrines Hills, which are located on the north side of the Yukon River near the Alaskan villages of Galena and Ruby. Personnel from the Alaska Departement of Fish and Game, U.S. Bureau of land Management, and U.S. Fish and Wildlife Service studied this herd from October 1983 to January 1990. The highest caribou count was 258 in June 1987. The proportion of newborn calves observed during the May calving period ranged from 0 to 28% (mean=10%) whereas it ranged from 4 to 17% (mean=13%) in October. Caribou inhabited mostly coniferous forest from October through April and open habitat from May through September. Male caribou occupied fewer habitat types, travelled less distance, and remained at lower elevations than female caribou. Management concerns for this herd are discussed.